Becoming society again: Reimagining new social contracts through Scandinavian creation theology. Issue 2 (7th June 2021) - Gerle, Elisabeth
Abstract: This article focuses on bodily care as the basis of economy. Drawing on Luther and Scandinavian Creation Theology, with an emphasis on shared situatedness and society, I discuss contemporary threats to welfare states. Conservative arguments in favor of family and small communities, combined with charity, provide a cultural/religious alibi for a global "neoliberalism, " where citizens are replaced by customers, and where power and resources from professions are transferred to controllers, due to the logic of NPM. In a critical discussion with Hannah Arendt, I argue that we need a politics that reinforce and develop new social contracts, national as well as international, based on an inclusive demos. A pre‐political Lutheran ethos can give inspiration to act for the common good, transcending any homogenous ethnos. The local and national are crucial for sustaining body and mind. However, this is increasingly combined with global and planetary entanglements. Interdependency reveals itself as planetary, where disappearing rain forests, melting icebergs, and the ongoing extinction of species are threats to our shared future. Therefore, rather than emphasizing the individual as a consumer on a global market with neutral administrators administering control and obedience, new kinds of contracts are needed. Core values of the pre‐political, such as care for bodily life and minds, may, in collaboration with national and international political assemblies, develop a planetary consciousness able to act for the common good, for a global demos with structures of solidarity.